2021
DOI: 10.1177/1476718x211030315
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood teachers’ perceptions and management of parental concerns about their child’s digital technology use in kindergarten

Abstract: Young children use, engage with, and experience digital technologies in their home and early childhood settings, yet their presence and use can be fraught with tensions and uncertainties. This paper reports on an Australian study focusing on how early childhood teachers perceive and manage parental concerns about their child’s digital technology use in kindergarten. Grounded theory was the methodological approach used to give insights into the early childhood teachers lived experiences. The findings revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Early life trauma encompasses a broad spectrum of adverse experiences that occur during the early stages of childhood and possess the potential to disrupt a child's fundamental sense of safety and security. These experiences, which may manifest in the form of physical, emotional, or sexual abuse, neglect, household dysfunction, exposure to violence, and various other forms of adversity, constitute the diverse range of events that fall under the umbrella of early life trauma (Schriever, 2020(Schriever, , 2021. Notably, there is a higher prevalence of early-life trauma in relation to experiences of interpersonal violation, specifically emotional, sexual, and physical abuses.…”
Section: Understanding Early Life Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Early life trauma encompasses a broad spectrum of adverse experiences that occur during the early stages of childhood and possess the potential to disrupt a child's fundamental sense of safety and security. These experiences, which may manifest in the form of physical, emotional, or sexual abuse, neglect, household dysfunction, exposure to violence, and various other forms of adversity, constitute the diverse range of events that fall under the umbrella of early life trauma (Schriever, 2020(Schriever, , 2021. Notably, there is a higher prevalence of early-life trauma in relation to experiences of interpersonal violation, specifically emotional, sexual, and physical abuses.…”
Section: Understanding Early Life Traumamentioning
confidence: 99%
“…Moreover, the integration of digital technologies in kindergarten settings has presented early childhood educators with a multitude of uncertainties and complexities to navigate (Schriever, 2020). Furthermore, parents have expressed concerns about their children's utilization of digital technology in kindergarten, thereby underscoring the tensions and uncertainties surrounding the presence and utilization of digital technologies in early childhood settings (Schriever, 2021). In addition, researchers have delved into the implications of young learners' attitudes towards the use of digital technologies in modern early childhood environments, emphasizing the necessity of comprehending child-computer interactions and the role of digital technologies in facilitating learning and development (Miller et al, 2019).…”
Section: The Impact Of Digital Technologies On Early Childhood Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…in our society; such diversity has implications in the relationships with the school. The literature identifies clear differences between the access of children to digital devices in their home environment and their early learning environment, i.e., educational centres (Schriever, 2021). Dashti and Yateem (2018) revealed that 78% of children in their study used mobile devices at home, whereas only 18% of them used mobile devices in their early learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…There are tensions when parents and schools have different meanings regarding the purpose of technologies and how children experiment with them. Parental control expands beyond the household and reaches the school, intervening and mediating the experiences of their children with technologies with the aim of preventing greater exposure and use of ICTs (Schriever, 2021). Furthermore, early childhood teachers, on the one hand, attend to and manage the concerns of the parents (Smith, 2020), and, on the other hand, they must make decisions on the digital technologies that are used by the children, renegotiating their meaning and guaranteeing that they are used with educational purposes, based on playing and active learning (Schriever, 2021b).…”
Section: Introductionmentioning
confidence: 99%